Noneruptive Unrest at the Caldera of Alcedo Volcano (Galápagos Islands) Revealed by InSAR Data and Geodetic Modeling. Issue 4 (4th April 2019) - Galetto, Federico; Bagnardi, Marco; Acocella, Valerio; Hooper, Andrew
Abstract: Understanding volcanic unrest is crucial to forecasting eruptions. At active mafic calderas unrest culminates in eruption more frequently than at felsic calderas. However, the mafic caldera of Alcedo Volcano (Ecuador) has experienced repeated episodes of unrest without erupting, since at least 1992, when geodetic monitoring began. Here we investigate the unrest that occurred between 2007 and 2011 using interferometric synthetic aperture radar (InSAR) data and geodetic modeling. We observe an initial asymmetric uplift of the southern caldera floor ( 30 cm of vertical motion) from 2007 to 2009, followed by subsidence of the uplifted area and contemporary uplift of the northwestern caldera rim between January and June 2010. Finally, from June 2010 through March 2011, caldera uplift resumed. The first uplift episode is best explained by inflation of a sill and the activation of an inner ring fault. Successive caldera subsidence and rim uplift are compatible with the withdrawal of magma from the previously inflated sill and its northwestern migration. The resumption of uplift is consistent with the repressurization of the sill. This evolution suggests episodic magma emplacement in a shallow reservoir beneath the caldera, with aborted lateral magma migration, probably due to the discontinuous supply from depth. This short‐term deformation pattern matches well geological observations showing a longer‐term (hundreds of years at least) asymmetric uplift of the caldera floor, culminating in a weak resurgence of 30 m. We propose that the monitored episodes of uplift represent short‐term stages of the rarely observed incremental growth of a resurgent basaltic caldera. Key Points: The 2007‐2011 noneruptive unrest at Alcedo was caused by shallow emplacement of new magma with limited lateral intrusion Uplift during unrest is similar in location and shape to the longer‐term weak resurgence of the caldera This unrest provides the rare opportunity to document the incremental growth of a basaltic resurgent caldera